Spatial regulation of a common precursor from two distinct genes generates metabolite diversity - Guo, Chun-Jun; Sun, Wei-Wen; Bruno, Kenneth S.; Oakley, Berl R.; Keller, Nancy P.; Wang, Clay C. C. (Chemical science (Cambridge), 2015)
In secondary metabolite biosynthesis, core synthetic genes such as polyketide synthase genes usually encode proteins that generate various backbone precursors. These precursors are modified by other tailoring enzymes to yield a large variety of different secondary metabolites. The number of core synthesis genes in a given species correlates, therefore, with the number of types of secondary metabolites the organism can produce. In our study, heterologous expression of all the A. terreus NRPS-like genes showed that two NRPS-like proteins, encoded by atmelA and apvA , release the same natural product, aspulvinone E. In hyphae this compound is converted to aspulvinones whereas in conidia it is converted to melanin. The genes are expressed in different tissues and this spatial control is probably regulated by their own specific promoters. Comparative genomics indicates that atmelA and apvA might share a same ancestral gene and the gene apvA is located in a highly conserved region in Aspergillus species that contains genes coding for life-essential proteins. Our data reveal the first case in secondary metabolite biosynthesis in which the tissue specific production of a single compound directs it into two separate pathways, producing distinct compounds with different functions. Our data also reveal that a single trans -prenyltransferase, AbpB, prenylates two substrates, aspulvinones and butyrolactones, revealing that genes outside of contiguous secondary metabolism gene clusters can modify more than one compound thereby expanding metabolite diversity. Our study raises the possibility of incorporation of spatial, cell-type specificity in expression of secondary metabolites of biological interest and provides new insight into designing and reconstituting their biosynthetic pathways.